2024
DOI: 10.1371/journal.pone.0299000
|View full text |Cite
|
Sign up to set email alerts
|

The concept of optimal planning of a linearly oriented segment of the 5G network

Viacheslav Kovtun,
Krzysztof Grochla,
Elena Zaitseva
et al.

Abstract: In the article, the extreme problem of finding the optimal placement plan of 5G base stations at certain points within a linear area of finite length is set. A fundamental feature of the author’s formulation of the extreme problem is that it takes into account not only the points of potential placement of base stations but also the possibility of selecting instances of stations to be placed at a specific point from a defined excess set, as well as the aspect of inseparable interaction of placed 5G base station… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Thirdly, numerous studies [ 8 , 15 17 ] have delved into the contention period for registration in the ‘initial ranging period' and the resource request for multicast/broadcast during the ‘resource request period'. [ 8 , 16 ] concluded that WiMAX achieves maximum throughput when a contention window size equals the number of competitive users' terminals.…”
Section: Introduction and State Of The Artmentioning
confidence: 99%
“…Thirdly, numerous studies [ 8 , 15 17 ] have delved into the contention period for registration in the ‘initial ranging period' and the resource request for multicast/broadcast during the ‘resource request period'. [ 8 , 16 ] concluded that WiMAX achieves maximum throughput when a contention window size equals the number of competitive users' terminals.…”
Section: Introduction and State Of The Artmentioning
confidence: 99%